Improving the Employment Process in Human Resource Department of XYZ Company in Quezon City : Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research provides information on the XYZ Company, including its history and mission statement. The company's logo reflects its commitment to serving its clients and consumers. The Company's Table of Organization shows the positions of knowledgeable people responsible for manufacturing high-quality products and the honourable administrators who monitor the process. The Department Procedural Stage depicts the flow of the department's processes, and the Employment section shows the current and needed personnel and their credentials. The Economic Growth Trend displays the company's current position and its readiness to minimize risk. The Key Competitor part lists competitors in the same industry and how the company deals with them, while the Industry Forecast section predicts the company's future performance.  A focus group method was used in conducting this study. The information was gathered from an HR staff member who shared the common problems and difficulties the company has been facing. All the information gathered is based on her knowledge of the company. The researchers made an agreement with the respondents to participate in the program they recommended to help improve the employment process in the human resources department of XYZ Company.  To enhance the system in the company, the researchers proposed a program that includes hiring a training officer to train newly hired employees, providing training, seminars, and team building for every employee, and creating an online hiring platform to easily hire quality employees without the help of a Manpower Agency. These proposed solutions will help the company improve their procedures and hiring process. The researchers found that the company should use jobstreet.com to handpick quality employees and provide training, seminars, and team building to lessen work-related stress. As Eren Davis said, "A happy employee is a productive employee."
Keywords: Employment; Process; Hiring; Training; Seminars